The analytical study of tuned mass dampers on the stability of KLCC skybridge / Ahmad Fauzi Ali - Ali, Ahmad Fauzi (1996)
The two storey skybridge walkway is proposed to span between Tower 1 and Tower 2 of the Kuala Lumpur City Centre development at the 41st and 42nd floors. The walkway is to have two pairs of cylindrical supporting legs below it which attach to the towers at the 29th floor. Vortex shedding may occur when the wind speed is such as to bring the shedding frequency close to the natural frequency of the body. In this case, oscillation start to build up to pressure fluctuations, caused by passing vortices, being in tune with a natural frequency of a skybridge leg. Once vortex shedding is established, the leg motion locks in the shedding frequency to the leg's natural frequency even if the wind speed varies slightly from the original speed that initiated the motion. A wind tunnel aeroelastic model test was done by RWDI to study the vortex shedding response of the legs. The vortex shedding motions of the east pair of skybridge legs were measured on a 1:70 scale aeroelastic model. Measurements were initially conducted for a wide range of wind direction at a damping ratio of 0.0015 to identify the wind directions producing the largest vortex shedding motions. From these tests, it was determine that the vortex shedding motions increase sharply below a damping ratio of about 0.004. Therefore, it would be important for the damping ratio on the actual skybridge legs to exceed 0.004 unless aerodynamic modifications are made. The damping ratio which the skybridge legs will exhibit cannot be analytically or empirically obtained with any certainty. However, it is likely to be somewhat lower than 0.004.